A Mathematical Model for the Dynamics of Onchocerciasis With Vector Control and Mass Drug Administration - Martin Karuhanga; Victor Yiga (Journal of Applied Mathematics)
In this paper, we investigate the transmission dynamics of onchocerciasis with asymptomatic infected humans using a mathematical model. The model incorporates interventions for treatment and vector control to evaluate the impact of these strategies. We analyse the model to determine the existence and stability of equilibrium points. Our results reveal that for the disease to persist in the community, the infection rate must exceed the sum of the treatment rate and the per capita death rate due to the disease. Sensitivity analysis highlights the critical role of the blackfly vector’s average daily biting rate in disease transmission. Numerical simulations indicate that administering highly effective drugs to infected individuals significantly reduces the number of cases. Therefore, in addition to vector control, the use of highly efficient drugs is crucial for controlling the transmission of river blindness.